(untitled) (American Journal of Islam and Society, 2002)
Over the decades, Nigerian political elites have devised various constitutional and administrative arrangements to cope with the country’s complex ethnic and religious pluralism. Yet, peace and stability have been elusive, as the country continues to experience severe religious and communal conflicts. These are reflected in the highly polemical book in which AdoKurawa tries to trace the origin and nature of what he calls the hostility of western Christian representatives towards Islam. In the book, Ado-Karuwa attempts to argue that the secular public space is too inflected with Christian values to make a claim to neutrality, and he uses Nigeria as a case study. He begins by noting that historically, Islam in Europe was tolerant and accommodative of the Christian religion, but this was not reciprocated when the Crusades were launched and "Muslims ... received the worst treatment imaginable." According to him, the failure of the armed campaign prompted Christian clerics to embark on an intellectual attack that entailed the negative representation of Islam in scholarly writings. What emerged, according to him, was a body of knowledge that explained the superiority of the West over the Islamic world. Contemporary global dominance by the West has also opened the door for academic institutions in Europe and America to strangulate Islam under the guise of promoting universal science. Ado-Karuwa relates the above to Nigeria by noting that, within the country, both Christian intellectuals and some British-trained Muslims act as agents of the West by promoting a secularism that marginalizes Islam. After a lengthy polemic about orientalism, colonialism, and American imperialism, the author returns to the issue of secularism, which he discusses generally without relating it concretely to Nigeria. He does not show how secularism in Nigeria marginalizes Islam; neither does he make efforts to show that secularism is tainted by Christian doctrines, in the manner done by Louis Dumont. Instead, he undermines his project by arguing that Christianity declined in Europe after secularism was enthroned by the Reformation and the Renaissance, and that in Sweden attendance in the Lutheran Church is only 5 percent. If it is true, as he argues, that the ...